Validity of Okun's law in Sri Lanka - Nadeshan, Perenparaj; Gnanachandran, Gnanachandran (International Journal of Business, Management and Economics, 2021)
The main goal of our research is to find out a relationship between the unemployment rate and the GDP growth rate in Sri Lanka according to Okun’s law and to know whether it can still be used as the best rule of thumb. This empirical analysis has employed the difference model, dynamic model, Error Correction Model (ECM) and Vector Error Correction Model (VECM) to validate the relationship between the unemployment rate and economic growth suggested by Okun's Law. The study is based on Quarterly data from 2004 Q1 to 2019 Q4. The results obtained through the application of varies econometric techniques such as Ordinary least square (OLS), Engel-Granger approach and cointegration procedure. The study finds that, Okun’s law is supported only by the cointegration analysis as expected by the Okun’s law in Sri Lanka. However, all other versions were reported negative Okun’s law coefficient signs while these results are not statistically significant. Overall this study is not able to found enough evidence to prove the inverse relationship between unemployment rate and economic growth rate in short run and able to found that Okun’s law can still be used as the best rule of thumb to describe the relationship between the unemployment and GDP growth in long term in Sri Lanka.